1996
DOI: 10.2134/agronj1996.00021962003600060017x
|View full text |Cite
|
Sign up to set email alerts
|

Spring Nitrogen Rate and Timing Influence on Seed Yield Components of Perennial Ryegrass

Abstract: Spring application of N generally increases seed yield of perennial ryegrass (Lolium perenne L.). Understanding the influence of N rates and timings on seed yield components can be used to improve N use efficiencies and seed yield. Field experiments during 1982 and 1983 at Oregon State University studied the effects of 60, 90, and 120 kg N ha−1, applied either at double‐ridge stage (DR) or at spikelet initiation stage (SI), on seed yield and yield components of the cultivar Pennfine. Control plots with no spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…Significant N loss due to volatilization and denitrification can also occur when large amounts of N are applied as a single application (Burt et al, 1993;Cookson et al, 2001). Applying N to match perennial ryegrass N demands during the growing season rather than single large applications could improve seed yields (Young et al, 1996;Kurcinka, 2009), improve seed quality (Cookson et al, 2000;Young et al, 1996), and potentially reduce environmental impacts of N fertilization by mitigating N loss (Cookson et al, 2000;Mullen et al, 2003).…”
mentioning
confidence: 99%
“…Significant N loss due to volatilization and denitrification can also occur when large amounts of N are applied as a single application (Burt et al, 1993;Cookson et al, 2001). Applying N to match perennial ryegrass N demands during the growing season rather than single large applications could improve seed yields (Young et al, 1996;Kurcinka, 2009), improve seed quality (Cookson et al, 2000;Young et al, 1996), and potentially reduce environmental impacts of N fertilization by mitigating N loss (Cookson et al, 2000;Mullen et al, 2003).…”
mentioning
confidence: 99%
“…If the application Table 1. [9,11,12] In our experiment, a distinct difference in shoot number, dry matter accumulation, and N content was found in the low-N and high-N treatments at the start of the experimental period (Table 1, Figs. changes N content and=or the biomass production, the original N rate is defined as insufficient for optimal growth, whereas if plants did not respond to an additional application, the original N rate was considered as sufficient.…”
Section: Discussionmentioning
confidence: 50%
“…[9][10][11][12] In addition, late application in plants with sufficient N available will cause increased growth of vegetative tillers [13] as well as early and strong lodging that can be detrimental for the seed yield. [9][10][11][12] In addition, late application in plants with sufficient N available will cause increased growth of vegetative tillers [13] as well as early and strong lodging that can be detrimental for the seed yield.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of N rate on seed yield sometimes depended on the SR, applying N at a rate of 157 kg ha −1 (even in combination with the lowest SRs) always resulted in seed yields equivalent to the top-yielding treatments (P < 0.05, Table 7). Previous research has shown that increased N availability can improve the number of seeds set per spike in perennial ryegrass, which is a primary factor driving seed yield (Young et al, 1996). Previous research has shown that increased N availability can improve the number of seeds set per spike in perennial ryegrass, which is a primary factor driving seed yield (Young et al, 1996).…”
Section: Yield Parameters and Seed Qualitymentioning
confidence: 99%
“…The effect of row spacing on yield and agronomic characteristics of perennial ryegrass in Minnesota has not been well characterized. Studies evaluating the effect of row spacing in various grass seed crops in China indicated that the number of seeds per spikelet, an important seed yield component (Young et al, 1996), increased with row spacing and that TSW for both Chinese sheepgrass (Leymus chinensis Trin. This can increase within-row tiller density, and the resulting increased plant-to-plant competition for light and nutrients in more densely planted rows could have an effect on plant growth (Kays and Harper, 1974;Deleuran et al, 2009;Han et al, 2013).…”
mentioning
confidence: 99%